Tata Kelola Kolaboratif Dalam Penanganan Pandemi Covid-19 Di Kota Padang - Geraldine Dwitiya Putri Kirana; M. Fachri Adnan (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The handling of the Covid-19 problem in the city of Padang has not been maximized. This is due to the lack of cooperation from various parties, from the government, private sector to the community. This study aims to explain the implementation of collaborative governance principles, and to explain the factors that influence the implementation of collaborative governance in handling the COVID-19 pandemic in Padang City. The research uses qualitative methods. In determining the informants used purposive sampling technique. In this study, interviews and documentation studies were used to obtain data. Data analysis was performed using manual data analysis procedure (MDAP) techniques. The validity of the data was tested by triangulation of sources. The results of the study indicate that the implementation of collaborative governance in handling the COVID-19 pandemic in the city of Padang has not been running properly. This can be seen from several principles that have been implemented well and there are also principles that have not been implemented properly. Factors that influence the implementation of collaborative governance are cultural factors and political factors.